Public interest, Personal data protection and Bank secrecy / Javni interes, zaštita ličnih podataka i bankovne tajne: A brief look at the Legal System of Bosnia and Herzegovina and Federation of Bosnia and Herzegovina / Kratki pregled pravnog sistema Bosne i Hercegovine i Federacije Bosne i Hercegovine - Sudžuka, Edina (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The secrecy and confidentiality of information are regulated by different laws. Secrets may be state, official, professional, business, and a law which regulates them determines degree of confidentiality, the scope of the protected rights, and its restrictions. The exercise of economic freedoms, the liberalization of commerce and globalization stimulate the international movement of people and capital, which in some cases, are aimed to escape from tax laws towards tax havens. Unrecorded financial transactions can result in, not only, double non-taxation but also in money laundering and terrorist financing. It is in the best interest of the every state to detect and prosecute organized crime actors and to prevent such activities from recurring. Keeping that in the mind, the emerging requirements aimed at creating global initiatives to combat financial fraud could be seen. In this regard, cooperation between states and the exchange of information on financial transactions and tax matters occur and develop. Bank secrecy stays as a more or less transparent screen in the space between public interest and private rights.